WOMEN’S EXPERIENCE IN USING “COMPLEMENTARY NURSING ON INFERTILITY” - Belet Lydia Ingrit (Saintika Medika, 2020)
The development of complementary therapies especially infertility treatment is increasing. A qualitative research was conducted to explore the experience of infertile women undergoing nursing complementary therapy. Eight women participated in this research were selected by purposive sampling method based on the inclusion criteria. Selection of participants was done using snowball sampling. Data were collected through in-depth interviews and field notes. Data analysis was performed using thematic content analysis and stages suggested by Collaizi. The results of this research  were: 1) Feeling of sadness was experienced by infertile women 2) Increasing age and the insistence of the family caused anxiety to infertile women, 3) Infertile women chose nursing complementary because they want to get pregnant naturally 4) Various ways and efforts were done by infertile women to get pregnant, 5) Infertile women had appropriate perception toward complementary nursing 6) Family supports were needed to succeed the complementary nursing. In conclusion, complementary nursing was very important to be chosen as one of solution for infertile couples. It is recommended that maternity nurses optimize their roles in giving information and support to infertile women.